Use of herbal products for weight loss in Turkey - Bellikci-Koyu, Ezgi; Şarer-Yürekli, Banu Pınar; Seckiner, Selda; Özdemir, Nilüfer; Buyuktuncer, Zehra (Progress in Nutrition, 2020)
Obesity treatment is a long-term challenge that requires a constant change in lifestyle and behaviors. Therefore, patients are usually interested in methods promising rapid weight loss. In this study, we aimed to determine the frequency of herbal product use by overweight and obese individuals for weight management. A cross-sectional study was conducted on 464 individuals admitted to an endocrinology clinic in a hospital in Turkey. Socio-demographic status, medical history, and information about herbal product usage were recorded by researchers using a data collection form.  The percentage of participants using herbal products for weight loss, was determined as 24.1% (n:112). Herbal product users were younger and had higher body mass index compared to non-users (p